Sudan in Focus: Newsletter for the Fragile and Conflict-Affected Food Systems Area of Work (November Issue) - Carrillo, Lucia; Hollerich, Gillian; Kosec, Katrina (CGIAR System Organization, 2025)
Across Africa, a recent resurgence of armed conflicts is driving up humanitarian needs while making aid delivery harder and more dangerous. Funding is not keeping pace: the United Nations’ Global Humanitarian Overview 2025 warns that a widening funding gap now threatens global response efforts, with the shortfall for humanitarian appeals reaching nearly US$37 billion by August 2025, the largest ever recorded.